Intact Fibroblast Growth Factor 23 Regulates Chronic Kidney Disease–Induced Myocardial Fibrosis by Activating the Sonic Hedgehog Signaling Pathway - Lanlan Li; Hua Gan (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Clinically, myocardial fibrosis is one of the most common complications caused by chronic kidney disease (CKD). However, the potential mechanisms of CKD‐induced myocardial fibrosis have not been clarified. Methods and Results In our in vivo study, a rat model of CKD with 5/6 nephrectomy was established. The CKD model was treated with the glioma 1 (Gli‐1) inhibitor GANT‐61, and myocardial fibrosis and serum intact fibroblast growth factor 23 levels were assessed 16 weeks after nephrectomy. Finally, we found that Gli‐1 and Smoothened in the Sonic Hedgehog (Shh) signaling pathway were activated and that collagen‐1 and collagen‐3, which constitute the fibrotic index, were expressed in CKD myocardial tissue. After administering the Gli‐1 inhibitor GANT‐61, the degree of myocardial fibrosis was reduced, and Gli‐1 expression was also inhibited. We also measured blood pressure, cardiac biomarkers, and other indicators in rats and performed hematoxylin‐eosin staining of myocardial tissue. Furthermore, in vitro studies showed that intact fibroblast growth factor 23 promoted cardiac fibroblast proliferation and transdifferentiation into myofibroblasts by activating the Shh signaling pathway, thereby promoting cardiac fibrosis, as manifested by increased expression of the Shh, Patch 1, and Gli‐1 mRNAs and Shh, Smoothened, and Gli‐1 proteins in the Shh signaling pathway. The protein and mRNA levels of other fibrosis indicators, such as α‐smooth muscle actin, which are also markers of transdifferentiation, collagen‐1, and collagen‐3, were increased. Conclusions On the basis of these results, intact fibroblast growth factor 23 promotes CKD‐induced myocardial fibrosis by activating the Shh signaling pathway.